KARAKTERISASI BENTONIT PACITAN - Buchari Buchari; Muji Harsini (Research Center for Chemistry - LIPI, 1996)
Bentonite is high plastivity and colloidal clay which contains smectite(montmorillonite) mineral as major the component. Commercially, there are two kinds of bentonite, which are calcium bentonite and sodium ben-tonite. Results of DTA, XRD and IR analysis on Pacitan bentonite, show that the major component is montmorillonite mixed with a little quartz. Cation exchange capacity (CEC), specific gravity, surface area, pore volume and swelling index of this bentonite are 45,98-62.42 meq/100 gram; 2,14-2,28 g/mL; 641,44-737,29 m /gram; 0,88-1,25 mL/gram and 78,95-163,16 %, respectively. Based on XRD and CEC value Pacitan bentonites are of the calcium bentonite type.